Determination of Coverage Oscillation for Inclined Communication Satellite - Ümit Cezmi Yılmaz; İbrahim Öz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The communication engineers need to evaluate footprint movement to deploy a ground station. Geostationary communication satellite’s inclination angle causes the movement of a satellite footprint. The calculation of the inclination angle requires complex astronomical knowledge and mathematical calculations. On the other hand, a satellite communication engineer does not need a very accurate inclination angle value to design a ground station for required service availability. We propose a practical method called trigonometric curve fitting for the inclination to solve the problem. The past and the future value of inclination can be evaluated by using the curve-fitting method. It is a simplified practical method and does not need advanced orbital dynamics knowledge. The orbit geometry and evaluated inclination angle are used for estimation of a coverage area movement. A satellite communication engineer can evaluate coverage area oscillation quickly and design a better link for an inclined orbit satellite by using the proposed method. We have evaluated the inclination angle of the communication satellite Sat-1 with the proposed method. Sat-1 spot beam movements and wide beam coverage area movements are estimated to obtain EIRP and G/T fluctuation for link budget purposes. The proposed method provides the results that are consistent with the results of measurements and the results of satellite operators’ professional tools.